The response of the connective tissue of the midpalatal suture of dogs to rapid and gradual expansion - Cruz, Sandra Regina L.; Tiongco, Ma. Teresa S.; Macapanpan, Luz C. (Adviser).
Hyrax palatal expanders were placed on four dogs to split the midpalatal suture. Two animals were sacrificed after a rapid expansion period of twenty-four hours. The other two were sacrificed after a gradual expansion period of twenty-four days. Sections of the midpalatal suture were studied under the microscope. Results of rapid expansion showed polymorphonuclear infiltration at the epithelium and connective tissue layer with immature connective tissue cells at the suture itself. Results of gradual expansion showed bone growth in the suture.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.